Antioxidant Effects of Selenium Nanoparticles Prepared from Eruca Sativa Extract on Ketoconazole –Induced Testicular Oxidative Damage in Male Rats - Q. Shareef, Basman; I. Al Qadhi, Huda; A. Jamal, Shayma’a (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Recent studies have shown that the anti-fertility effects of Ketoconazole can be minimized by taking an antioxidant nanoparticles based-plant extract in combination with the medication or by taking it after medication. One of the effective methods to improve its medicinal properties and decrease the toxicities of Selenium is by formulating it as nanoparticles. However, this is still a challenging strategy. Objectives: The aim of this study was to analyze the impact of nano selenium, which was prepared from Eruca Sativa extract, on testicular oxidative stress parameters in rats that were treated with ketoconazole. The study will focus on the evaluation of glutathione peroxidase, superoxide dismutase, and malondialdehyde as indicators of oxidative stress. Methods: In this study, a 1% w/v solution of plant extract was added to a solution of 10mM sodium selenite in different ratios, and placed on a magnetic stirrer in the dark for 12 hours at a temperature 50Cº and pH9. The solution was then left for 48 hours, and the optimal fabricated selenium nanoparticles were selected for further characterization. forty-eight rats were divided into six groups with eight animals in each. Group A was the negative control, while Group B was given oral Ketoconazole at a dose of 50mg/kg for fourteen days. Group BC, BD, BE1 and BE2 were given oral Ketoconazole at a dose of 50 mg/kg for fourteen days, followed by 200mg/kg Eruca Sativa, 0.5mg/kg oral sodium selenite, 0.25mg/kg oral nano selenium and 0.5mg/kg oral nano selenium for 28 days, respectively. Finally, the animals were euthanized and their testicle anti-oxidant parameters were evaluated. Results: Significant increases in glutathione peroxidase and superoxide dismutase ( p value < 0.001), and a decrease in malondialdehyde levels ( p value < 0.001) were observed in groups treated with nanoparticles compared to control group. Conclusion: Nano forms of prepared by Eruca sativa extract exhibit significant antioxidant effects on testicular tissues, while being available for several metabolic, biological, and physiological functions.